Extracorporeal membrane oxygenation in pheochromocytoma-induced cardiogenic shock. (May 2018) - Bouabdallaoui, Nadia; Bouchard, Denis; Jolicoeur, E. Marc; Chronopoulos, Alexandra; Garneau, Pierre Y; Lamarche, Yoan
Extracorporeal membrane oxygenation has been extensively used for cardiopulmonary support in cardiogenic shock. However, its clinical value in the management of pheochromocytoma crisis remains unclear. We report a rare case of life-threatening cardiogenic shock managed with peripheral venoarterial extracorporeal membrane oxygenation combined with endovascular left ventricular venting, in a 40-year-old female patient, in the setting of unknown adrenal pheochromocytoma. We highlight the life-saving role of extracorporeal membrane oxygenation in undiagnosed endocrine emergencies, allowing cardiac and end-organ recovery, and giving time for accurate diagnosis and specific treatment in such unusual situations.